(3GdJYQjaGJs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO agPg JYQjaGJ LeYJgG hGUWdGMGJ GNPJgG ef cJH Gdbhe hQJHJgG Ydi MQha GdgLGA ef GdCda hGdHGA Edi GdjGA JSgjdkG SChdgG ddWGdHjf s
(3BNQgG (B:s
(3jfJgi CKfGA aUd GdcGa s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B422s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs